The Effect Of Giving Edamame Nuts On The Improvement Of Breast Milk Production In Postpartum Women - Dewi Sartika; Fina Kusuma Wardani; Afrahul Padilah Siregar (Science Midwifery, 2022)
Breast milk is the first natural food for babies. Breast milk provides all the energy and nutrients a baby needs for the first months of life. Lack of breast milk production results in the practice of breastfeeding in infants is not met. The purpose of this study was to find out the effect of edamame beans on the production of breast milk in postpartum mothers at the Midwife Clinic. This research uses Quasy Eksperiment Design using one Group Pretest-Postest Design. The population in this study is all postpartum mothers day 3-10 amounted to 6 people and a sample of 6 people. this research uses purposive sampling technique with univariate and bivariate analysis. The results of the study obtained from data analysis with Wilcoxon test showed in mothers who postpartum can be concluded pre-test and post-test edamame beans. The results in the table are known that the value of P- value (0.025) < α0.05 then H0 rejected Ha received which means there is an influence of pre-test and post-test on the administration of edamame beans on the production of breast milk in postpartum mothers in the Midwife Clinic. The conclusions in this study showed the results that there is an influence of edamame beans on the production of breast milk in postpartum mothers.